Hubungan Penggunaan Smartphone Dan Frekuensi Bermain Game Online Dengan Kejadian Astenopia Pada Anak SMA Negeri 22 Di Wilayah Kerja Puskesmas Bentiring Kota Bengkulu Tahun 2025 - Shintia Putri Deyasa; Diyah Tepi Rahmawati; Danur Azissah RS (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The use of digital devices involving intensive visual activity has become an emerging eye health concern. The World Health Organization reports that approximately 40–90% of individuals engaged in high visual activity experience eye fatigue. In Indonesia, the prevalence of visual impairment reaches 4.8%, while internet usage has covered 79.5% of the population, including children and adolescents. High exposure to digital screens among school-aged individuals increases the risk of developing Asthenopia. This study aimed to determine a correlation between smartphone use and the frequency of playing online games with the incidence of asthenopia. This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 61 respondents selected using stratified random sampling technique. The research instruments included questionnaires on smartphone use, frequency of playing online games, and asthenopia measured using the Visual Fatigue Index. Data analysis was conducted using univariate analysis, bivariate analysis with the Chi-Square test, and multivariate analysis using binary logistic regression. The univariate results showed that most respondents had a moderate level of smartphone use (59.0%) and a low frequency of playing online games (50.8%). A total of 45.9% of respondents experienced asthenopia. Bivariate analysis revealed a significant correlation between smartphone use and asthenopia (p = 0.000), as well as between the frequency of playing online games and asthenopia (p = 0.000). The researchers recommend that Bentiring Health Center and schools enhance eye health education through counseling programs, regulate the duration of smartphone use, and encourage periodic eye rest to prevent asthenopia.